Cracking the GRE - Edited By Shelton, Meave (New York Penguin Random House, 2017)
Everything students need to know to master the Verbal Reasoning, Quantitative Reasoning, and Essay sections of the GRE (Graduate Record Examination) plus access to extra tests, practice drills, guidance, and review in our Premium Portal online.
Keywords: Graduate Record Examination -- United States -- Universities and colleges--Graduate work--Entrance examinations